Fostering Religious Values through a Sociocultural Approach within the Community of Camba Berua, Makassar - M. Ilham Muchtar; A Asdar; M Chiar Hijaz (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Religious development among lower-income communities presents unique challenges and characteristics. The main issues encountered include cultural factors and limited living conditions, which often make these communities closed and exclusive. Therefore, implementing religious development within such communities requires a special paradigm and approach. This research is a field study employing a qualitative approach aimed at exploring data obtained directly from the field. The data were collected through observation, interviews, and document analysis, then analyzed descriptively to provide an overview of Religious Development through a Sociocultural Approach in the Community of Camba Berua Sub-district, Makassar City. The findings reveal that in the context of spiritual development—particularly among lower-income communities—the sociocultural approach model plays a crucial role. Every community possesses its own culture, which not only represents their creative expression but also serves as a social bond that fulfills their collective needs. The sociocultural approach in spiritual development is more accommodative toward specific cultural values in an innovative and creative way, without diminishing the essential aspects of religiosity. This model is particularly suitable for the community of Camba Berua in Ujung Tanah District, Makassar City. At least two forms of sociocultural approaches can be applied in religious development: the comprehensive approach and the sympathetic-suggestive approach. The comprehensive approach implies that the internalization of religious values within a community should consider the existing social and cultural values of its environment. The sympathetic-suggestive approach emphasizes creating a comfortable and non-threatening atmosphere during the process of religious development. Ultimately, religious community development aligns with one of the Sustainable Development Goals (SDGs), particularly in promoting Quality Education.